Performance Enhancement Of Etc By Changing Water Film Thickness. - et. al., Mohamed A. Essa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The vital demand of fresh water across the world lead researcher to look for solution. This experiment introduces a new design solar still system in which a traditional solar still is replaced by ETC. ETC as a solar desalination system provide a simple and economical solution. Water film thickness inside ETC changed (6mm and 8mm) to decide which one gives the highest thermal efficiency. Result showed that the ETC with water film thickness of 6 mm achieved the highest efficiency of 23% and the production of fresh water reaches up to 0.299 kg per day.